Fluorescent imaging of nitric oxide production in neuronal varicosities associated with intraparenchymal arterioles in rat hippocampal slices. - Brown, L; Key, B; Lovick, T (2000)
The fluorescent indicator 4,5-diaminofluorescein (DAF-2) has been used to investigate the production of nitric oxide in the vicinity of intraparenchymal cerebral blood vessels. Slices of rat hippocampus 300-350 microm thick, were loaded with 5 microM DAF-2 diacetate. On exposure to light of 450-490 nm wavelength, point sources of fluorescence, 1.8+/-0.2 microm in diameter (mean+/-SEM), were observed in close apposition to the outer surface of the vascular smooth muscle wall of 10/15 arterioles. In fixed slices, resectioned and processed for nicotinamide adenine dinucleotide phosphate-dependent diaphorase, stained varicose fibres were also seen in close association with the smooth muscle wall of small arterioles. These findings suggest that tonic activity in perivascular nitrergic nerve fibres lying in close proximity to intraparenchymal microvessels may be a source of dilator tone within the parenchyma.